Longitudinal relationship between baseline Weight-Adjusted Waist Index and stroke risk over 8 years in Chinese adults aged 45 and older: a prospective cohort study - Xiaoqiang Li; Xiangmao Zhou; Hui Du; Hui Wang; Zhijian Tan; Yaqing Zeng; Zhibin Song; Guifeng Zhang (Frontiers in Public Health)
BackgroundThis study explores the longitudinal relationship between the Weight-Adjusted Waist Index (WWI), an innovative obesity metric, and stroke incidence in aged 45 and older Chinese adults.MethodsData from 9,725 individuals aged 45 years and older were analyzed from the China Health and Retirement Longitudinal Study (2011–2020). Baseline characteristics were analyzed across different quartiles of the WWI. Stroke incidents were determined through self-reported doctor diagnoses. Multivariate logistic regression analyses and curve fitting assessed the WWI-stroke risk relationship, adjusting for various demographic, lifestyle, and health-related factors.ResultsHigher WWI quartiles were associated with older age and higher prevalence of stroke and adverse health conditions. In the fully adjusted model, participants in the highest WWI quartile had an odds ratio of 1.52 (95% CI: 1.19, 1.92) for stroke compared to the lowest quartile. Curve fitting revealed a linear relationship between WWI and stroke risk, consistent across various demographic and clinical subgroups.ConclusionHigher WWI is linked to an increased risk of stroke in aged 45 and older Chinese adults over an eight-year period. WWI may serve as an effective tool for predicting long-term stroke risk within this population. However, the study is limited by the reliance on self-reported stroke diagnoses and the presence of potential residual confounding factors.